Answers

2015-07-08T15:59:11+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Ans is k= -3
x  =  1
then
4(1)^3+3(1)^2-4(1)+k=0
4+3-4+k=0
3+k=0
k=-3
1 1 1
Sorry to say bt i dont understood your solution.....
its ohk ra
The Brainliest Answer!
2015-07-08T15:59:23+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
P(x)=4x^3 + 3x^2 - 4x + k Then, p(1)=4(1)^3 + 3(1)^2 - 4(1) + k =4 + 3 - 4 +k =3 + k=0 or k=(-3)..........I hope this answer helps you.....Be happy....
1 5 1